Analysis of the Science Literacy Profile of Students at State Junior High School - Sintha Eka Ashari; Fida Rachmadiarti; Nuniek Herdyastuti (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This study aims to determine the achievement of scientific literacy skills of junior high school students in the competency aspect. The competency aspects measured in this study are the competence to explain scientific phenomena, interpret data and scientific evidence, and evaluate and design. Methods: The research was conducted using the test method. The data was collected using a competency aspect scientific literacy test using a multiple choice test of 20 items on the scientific literacy test. The sampling technique used stratified random sampling, amounting to 67 students. Data analysis techniques using quantitative descriptive. Results: Based on the research conducted by the results of data analysis, it was found that the scientific literacy aspect of students' competence was included in the low category, with an overall average of 55.15%. The aspects of scientific literacy competency measured in this study are explaining scientific phenomena, interpreting data and scientific evidence, and evaluating and designing. The results of each scientific literacy competency indicator are as follows: (1) students' ability to explain scientific phenomena, the average percentage only reaches the deficient category; (2) students' ability to interpret data and scientific evidence in the deficient category and (3) students' ability to evaluate and design in the deficient category. Novelty: This study reveals an urgent need to develop appropriate innovations, methods, and designs to improve students' science literacy, especially the learning models used. These findings encourage teachers to improve learning continuously.